2015
DOI: 10.1186/s12906-015-0718-0
|View full text |Cite
|
Sign up to set email alerts
|

Optimization protocol for the extraction of 6-gingerol and 6-shogaol from Zingiber officinale var. rubrum Theilade and improving antioxidant and anticancer activity using response surface methodology

Abstract: BackgroundAnalysis and extraction of plant matrices are important processes for the development, modernization, and quality control of herbal formulations. Response surface methodology is a collection of statistical and mathematical techniques that are used to optimize the range of variables in various experimental processes to reduce the number of experimental runs, cost , and time, compared to other methods.MethodsResponse surface methodology was applied for optimizing reflux extraction conditions for achiev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 30 publications
(25 reference statements)
3
36
0
1
Order By: Relevance
“…Microwave-dried extract showed the highest quantity (1.5 fold) in TPP, [6]-gingerol content, and antioxidant activity when compared with the cross-flow dried extract (Kubra & Rao, 2012a). Moreover, a study focusing on extraction procedures for gingerol demonstrated that extraction temperature (50-80°C) and extraction time (2-4 hr) are also important aspects (Ghasemzadeh, Jaafar, & Rahmat, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Microwave-dried extract showed the highest quantity (1.5 fold) in TPP, [6]-gingerol content, and antioxidant activity when compared with the cross-flow dried extract (Kubra & Rao, 2012a). Moreover, a study focusing on extraction procedures for gingerol demonstrated that extraction temperature (50-80°C) and extraction time (2-4 hr) are also important aspects (Ghasemzadeh, Jaafar, & Rahmat, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…In industrial process control, response surface methodology (RSM) is usually used to determine the levels of input variables that optimize a particular response [1820]. RSM is a technique that consists of: (a) designing experiments to deliver adequate and reliable response measurements, (b) developing a mathematical model with the best fit to the data obtained from the experimental design, and (c) determining the optimal value of the independent variables that produce the maximum or minimum values of the response.…”
Section: Introductionmentioning
confidence: 99%
“…The most abundant form of shogaol is 6‐shogaol (Jolad et al ., ). The major active components 6‐gingerol and 6‐shogaol have a number of pharmacological activities, including antinausea, antiinflammatory, carminative, and antiemetic activities (Ghasemzadeh et al ., ).…”
Section: Discussionmentioning
confidence: 99%